Effects of chronic stress on the activity of ATP-AZ in cells of immune response in rats and correcting the possibility of internal energy exchange reception mineral water - Zmievsky, A. V.; Nasibullin, B. A.; Guscha, S. G. (Journal of Education, Health and Sport, 2015)
Zmievsky A. V., Nasibullin B. A., Guscha S. G. Влияние хронического стресса на активность системы АТФ-АЗ в клетках иммунного ответа у крыс, и возможность коррекции нарушений энергетического обмена внутренним приёмом минеральных вод = Effects of chronic stress on the activity of ATP-AZ in cells of immune response in rats and correcting the possibility of internal energy exchange reception mineral water. Journal of Education, Health and Sport. 2015;5(4):129-134. ISSN 2391-8306. DOI: 10.5281/zenodo.16686 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A129-134 https://pbn.nauka.gov.pl/works/553740 http://dx.doi.org/10.5281/zenodo.16686 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.03.2015. Accepted: 27.03.2015. Влияние хронического стресса на активность системы АТФ-аз в клетках иммунного ответа у крыс, и возможность коррекции нарушений энергетического обмена внутренним приёмом минеральных вод EFFECTS OF CHRONIC STRESS ON THE ACTIVITY OF ATP-AZ IN CELLS OF IMMUNE RESPONSE IN RATS AND CORRECTING THE POSSIBILITY OF INTERNAL ENERGY EXCHANGE RECEPTION MINERAL WATER А.В. Змиевский, Б.А. Насибуллин, С.Г. Гуща A.V. Zmievsky, B.A. Nasibullin, S.G. Guscha Украинский научно-исследовательский институт медицинской реабилитации и курортологии МЗ Украины, Одесса Ukrainian Research Institute of Medical Rehabilitation and Balneology, Odessa Abstract The authors of the model when playing immobilization - emotional stress in animals have revealed abnormalities in energy supply in the organs of the immune response. The authors demonstrated the possibility of correction of stress caused by disorders of energy metabolism in thymocytes and splenocytes using the mineral waters of different chemical composition. Keywords: energy metabolism, mineral water, thymocytes, splenocytes. Реферат Авторы при воспроизведении модели иммобилизационно-эмоционального стресса у животных выявили нарушения в энергообеспечении в органах иммунного ответа. Авторами была показана возможность коррекции стресс-обусловленных нарушений энергетического обмена в тимоцитах и спленоцитах при помощи минеральных вод разного химического состава. Ключевые слова: энергетический обмен, минеральные воды, тимоциты, спленоциты.